2010
DOI: 10.2166/wst.2010.044
|View full text |Cite
|
Sign up to set email alerts
|

Benchmark Simulation Model No 2: finalisation of plant layout and default control strategy

Abstract: The COST/IWA Benchmark Simulation Model No 1 (BSM1) has been available for almost a decade. Its primary purpose has been to create a platform for control strategy benchmarking of activated sludge processes. The fact that the research work related to the benchmark simulation models has resulted in more than 300 publications worldwide demonstrates the interest in and need of such tools within the research community. Recent efforts within the IWA Task Group on "Benchmarking of control strategies for WWTPs" have f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
88
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(90 citation statements)
references
References 7 publications
1
88
0
1
Order By: Relevance
“…In 2007, the Benchmark Simulation Model No. 2 (BSM2) (Jeppsson et al, 2007;Nopens et al, 2010) was proposed by integrating the BSM1 with wastewater pre-treatment and a sludge train (Fig. 1).…”
Section: Brief Historical Overview Of Plant-wide Modellingmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2007, the Benchmark Simulation Model No. 2 (BSM2) (Jeppsson et al, 2007;Nopens et al, 2010) was proposed by integrating the BSM1 with wastewater pre-treatment and a sludge train (Fig. 1).…”
Section: Brief Historical Overview Of Plant-wide Modellingmentioning
confidence: 99%
“…on such performance indicators as EQI, OCI, and GHG emissions. Sweetapple et al (2013) presented the BSM-e, a modified version of BSM2 (Jeppsson et al, 2007) that is able to quantify on-site and off-site GHG emissions from a WWTP with the same configuration as the BSM2 (as detailed by Jeppsson et al, 2007 andNopens et al, 2010; Table 1). The BSM-e model differs from the BSM2G because it includes foursteps for denitrification, as detailed by Samie et al (2011), including stripping of N 2 O and CO 2 emissions, as suggested by Monteith et al (2005) (Table 1).…”
Section: Dynamic Mechanistic Modelsmentioning
confidence: 99%
“…Originally, the same weighting factors were assigned to both TKN and NO 3 − , leading to the problem that a process control that achieves low concentrations of TKN in the effluent would not be rewarded. However, from an ecological point of view, low concentrations of TKN in the effluent are clearly preferential and, therefore, the weighting factors have been adapted accordingly [1,24].…”
Section: Effluent Quality Index (Eq) Used In Bsm Nomentioning
confidence: 99%
“…Based on studies performed using the BSM No. 2, it was derived that the process control that regulates the O 2 concentration in two aeration tanks each to 2 gO 2 /m [24]. In their work, Vanrolleghem and Gillot conclude that the dissolved O 2 concentration should be controlled in every aeration tank as the performance, measured by the EQ improves significantly compared to the open-loop strategy [25].…”
Section: Introductionmentioning
confidence: 99%
“…Because the WWTP proved to be overloaded resulting in a violation of the effluent limits of more than 60%, the total volume of the reactors was increased from 6749 m 3 to 15000 m 3 . As a result, each aerated reactor (R5, R6 and R7) had a volume of 3000 m 3 and each anoxic reactor (R3 and R4) had a volume of 1500 m 3 as presented in Nopens et al (2010). The aeration was modeled using the volumetric mass transfer coefficient (k L a).…”
Section: Simulated Plant Descriptionmentioning
confidence: 99%